2018
DOI: 10.1029/2018ms001441
|View full text |Cite
|
Sign up to set email alerts
|

WISHE‐Moisture Mode in an Aquaplanet Simulation

Abstract: This study aims to understand the nature of the tropical intraseasonal oscillations (ISOs) in an aquaplanet simulation performed using Geophysical Fluid Dynamics Laboratory's AM2.1 with a uniform sea surface temperature within the deep tropics. The simulated ISO resembles the observed Madden‐Julian Oscillation in that the spectral peak in precipitation appears at zonal wave number 1 and a period of ~60 days. Vertically integrated moist static energy budget of the simulated ISO shows that enhanced latent heat f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 55 publications
7
35
1
Order By: Relevance
“…But in their updated analysis, Fuchs and Raymond (2017) identified WISHE as the main mechanism for driving the MJO, though cloud-radiation interactions further destabilized the model. This is also consistent with mechanism denial experiments conducted with an atmospheric general circulation model with fixed, constant sea surface temperature, by Shi et al (2018). KE18's linear model showed an MJO-like mode destabilized by cloud-radiation interaction and driven eastward by WISHE, and Kelvin modes driven mostly by WISHE.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…But in their updated analysis, Fuchs and Raymond (2017) identified WISHE as the main mechanism for driving the MJO, though cloud-radiation interactions further destabilized the model. This is also consistent with mechanism denial experiments conducted with an atmospheric general circulation model with fixed, constant sea surface temperature, by Shi et al (2018). KE18's linear model showed an MJO-like mode destabilized by cloud-radiation interaction and driven eastward by WISHE, and Kelvin modes driven mostly by WISHE.…”
Section: Introductionsupporting
confidence: 85%
“…Numerical experiments using full-physics global and near-global models suggest that cloud-radiation interactions (Arnold and Randall 2015;KE18;Kim et al 2011) and WISHE (Shi et al 2018) are essential to lowfrequency equatorial modes such as the MJO. When radiative heating and/or surface wind is horizontally homogenized in these models, the low-frequency modes largely or completely disappear.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Note that while the wind-induced surface heat exchanges (WISHE) mechanism has been found to be critical for the MJO-like intraseasonal variability in several recent aqua-planet modeling studies 34,35 , this process does not seem essential for the intraseasonal variability simulated in ECHAM AGCM in this study. The amplitude of anomalous surface heat fluxes associated with intraseasonal variability in both QOBS and FLAT are rather weak compared to the vertically integrated moisture tendencies by horizontal advection and column processes ( Supplementary Fig.…”
Section: Physical Mechanisms Underlying Distinct Mjo Propagationmentioning
confidence: 55%
“…Analytical linear models are limited by their design in capturing all the characteristics of the MJO. Shi et al () and Khairoutdinov and Emanuel () found compelling evidence that WISHE‐moisture mode is associated with the MJO. Shi et al () simulated the MJO using Geophysical Fluid Dynamics Laboratory's AM2.1 on an aquaplanet.…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al () and Khairoutdinov and Emanuel () found compelling evidence that WISHE‐moisture mode is associated with the MJO. Shi et al () simulated the MJO using Geophysical Fluid Dynamics Laboratory's AM2.1 on an aquaplanet. Based on series of denial experiments they showed that the MJO cannot be simulated unless WISHE was included.…”
Section: Introductionmentioning
confidence: 99%